EP920 Ovarian cancer and BRCA mutation typing: a review of cases in northern ireland 2018. (1st November 2019) - Mcinerney, J; Rainey, L; Popa, G; Robinson, M; Harley, I
Abstract : Introduction/Background: Identification of BRCA mutation is important in the treatment of advanced ovarian cancers. It can improve efficacy of therapies; provide prognostic information and earlier identification in predisposed families. Aim: To identify the incidence of ovarian cancer in 2018; the variations in histolopathology and the referral rate for genetic testing. Methodology: Cases were identified through the Cancer Patient Pathway System. Demographic information collected included: age and stage at diagnosis; subtype; family and personal cancer history; referral date for, and date of genetic testing as well as result date and genetic mutation. Results: There was an incidence of 104 cases. Average 65.7 years (range: 37–93). Cancer stages 1 to 4 had incidence 13.5%: 11.5%: 52%: 23% respectively. High grade serous carcinoma was the most common histological variant with 76%; endometrioid 10%; clear cell carcinoma 9%; low grade serous carcinoma 5%. 12.5% and 19% of cases had a family history of ovarian or breast cancer respectively, while 66% of cases report a direct family history of cancer. 8 patients reported a breast cancer history and 4 had a history of other cancers. 59% of cases were referred for genetic testing. 41 patients received testing. 10 patients await testing and 10 patients declined or died. Of the 41 cases tested only 3 patients were identified as BRCA 1 or BRCA 2 mutations. Conclusion: The majority of cases presenting were advanced stage disease. These represent patients who would benefit from genetic targeted drug therapies or BRCA family identification yet only 59% of cases were referred and only 40% actually received testing by the time of reporting. Interestingly however, 7% of those tested were BRCA positive. This study highlights the need to further understand our populations' genetic predispositions to ovarian cancer in an effort to improve cancer care for patients and their families. Disclosure: Nothing to disclose.